Highly Selective Separation of CO2 and H2 by MIL-88A Metal Organic Framework - Ngoc Son, Do; Thi Xuan Huynh, Nguyen; Thoai, Nam; Trung Kien, Pham (VNU Journal of Science: Mathematics - Physics; Vol 37 No 3, 2021)
CO 2 capture is indispensable for a cleaner environment and the mitigation of global warming. The pre-combustion CO 2 capture relates to the separation of CO 2 from H 2 in the syngas mixture. Recently, metal-organic frameworks have proven to be excellent candidates for this purpose. In the current work, MIL-88A (Fe, V, Ti, Sc) were studied for the first time by using the grand canonical Monte Carlo simulations for the CO 2 /H 2 mixture. The adsorption capacity of CO 2 and H 2 in the absence and presence of water medium in MIL-88A was analyzed. We found that the magnitude of the CO 2 capacity is many times higher than that of the H 2 capacity, which leads to rather high CO 2 /H 2 selectivity. The presence of water decreases the maximum selectivity of MIL-88A(Fe), increases that of MIL-88A(Ti and Sc), while it influences differently on the maximum selectivity of MIL-88A(V) for the different CO 2 /H 2 mole fractions. The order of the maximum selectivity was found to be MIL-88A(Sc) > MIL-88A(Ti) > MIL-88A(V) > MIL-88A(Fe). The MIL-88A(Sc) achieved the maximum CO 2 /H 2 selectivity of ~ 900 and 1300 in the absence and the presence of water medium, respectively. These values are significantly higher than those of many well-known metal-organic frameworks. The favorable adsorption sites of the CO 2 /H 2 mixture in MIL-88A were also elucidated.